Sequences of Reverse Transcribed Brain DNA Are Modified by Learning - Giuditta, Antonio; Casalino, Joyce (Frontiers in Molecular Neuroscience, 2020)
Brain metabolic DNA (BMD) is continuously synthesized by reverse transcription in presynaptic synaptosomes and astroglia, and is partly transferred to nuclei after acquiring the double stranded configuration. Synthesis and turnover of BMD are markedly dependent on brain activity, as shown by circadian oscillations, environmental enrichment and impoverishment, and a variety of learning protocols. In rodents learning a two-way active avoidance task, BMD synthesis doubles, thus raising the possibility that sequences of learning BMD may differ from control BMD. The hypothesis has now been examined by sequencing cytoplasmic BMD. The present data indicate that most high-quality mapped BMD fragments hosting more than seven sequences are present in all mice. Three of them are exclusively present in learning BMD and four in control BMD. In addition, the annotated genes closest to them are mostly involved in modulating synaptic activity. The data support the conclusion that learning BMD sequences encode brain responses to the modified environment.